IN VITRO ANTIOXIDANT ACTIVITY OF TERMINALIA CATAPPA NUTS - KRISHNAVENI, MARIMUTHU (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The main objective of the study is to assess the secondary metabolites and antioxidant activities of Terminalia catappa nut as it is not a commercialized nut. Methods: The secondary metabolites and antioxidant activities were experimented by adopting recommended standard procedures using aqueous extract of Terminalia catappa nut powder- 25, 50, 75, 100mg. Results: The total phenolics content was higher on comparison with flavonoid content. Likewise, among the antioxidant activities, nitric oxide scavenging (257.33±2.30mg/g) as well as reducing power activity (142.66±6.11mg/g) was higher compared to total antioxidant (82.66±6.11mg/g) and metal chelating activity (64.66±2.30mg/g). Conclusion: The results obtained shows that it contains phenolics and flavonoid, which in turn induces antioxidant activities. Hence, this might act as a potential antioxidant, and needs further characterization and purification. Key words: Antioxidant, Aqueous extract, Nuts, Secondary metabolites, Terminalia catappa